Risk factors for scald injury in children under 5 years of age: a case–control study using routinely collected data - Shah, M.; Orton, Elizabeth; Tata, L.J.; Gomes, C.; Kendrick, D. (Elsevier, 2013)
Scald injury is common, accounting for half of all burns in pre-school children. Most scalds are preventable and health professionals can play an important role in targeting interventions to those at greatest risk. However, the potential for routinely collected medical data to be used to identify high risk children has not been well explored.